2011
DOI: 10.1002/adma.201003188
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Transparent Electrodes Based on Thin Films of Carbon Nanotubes, Graphene, and Metallic Nanostructures

Abstract: Transparent electrodes are a necessary component in many modern devices such as touch screens, LCDs, OLEDs, and solar cells, all of which are growing in demand. Traditionally, this role has been well served by doped metal oxides, the most common of which is indium tin oxide, or ITO. Recently, advances in nano-materials research have opened the door for other transparent conductive materials, each with unique properties. These include CNTs, graphene, metal nanowires, and printable metal grids. This review will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
1,795
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,085 publications
(1,818 citation statements)
references
References 279 publications
(347 reference statements)
7
1,795
1
15
Order By: Relevance
“…42 During the past few decades, graphene has been well-investigated and much work has been devoted to the synthesis, structures, properties, and possible applications of graphene. [43][44][45] Less work has been directed to the surface wetting behavior of graphene, although the wetting behavior of solid surfaces is a very important aspect of materials and can strongly affect their properties. 46 Recently, the wettability of graphene lms could be tuned from superhydrophobic to superhydrophilic by simply controlling the relative proportion of acetone and water in the solvent, which is important to expand the applications of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…42 During the past few decades, graphene has been well-investigated and much work has been devoted to the synthesis, structures, properties, and possible applications of graphene. [43][44][45] Less work has been directed to the surface wetting behavior of graphene, although the wetting behavior of solid surfaces is a very important aspect of materials and can strongly affect their properties. 46 Recently, the wettability of graphene lms could be tuned from superhydrophobic to superhydrophilic by simply controlling the relative proportion of acetone and water in the solvent, which is important to expand the applications of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The need for aggressive acid treatments to induce p-type doping of semiconducting tubes and the non-permanent nature of the doped state are also problematic. 16 Graphene is another potential TCE material amongst the carbon allotropes, with Bae et al having reported 30-inch graphene films with sheet resistances of 30 Ω sq. -1 at transmittances of ~90 %.…”
mentioning
confidence: 99%
“…2D macroscopic graphene hybrid films with excellent mechanical strength, superb electric conductivity, and excellent chemical stability have been widely studied for transparent conductive films,66, 67, 68, 69 flexible SC electrodes,70 sensors,71 and other applications 72. For instance, Gao and co‐workers designed graphene/multiwalled carbon nanotube (MWCNT) membranes by assembling refluxed GO and MWCNTs on a porous substrate via simple filtration‐assisted assembly73 with an increased water flux compared to the previously reported neat graphene nanofiltration membrane 74.…”
Section: Self‐assembled Graphene‐based Hybrid Structuresmentioning
confidence: 99%